A Comparative Study on the Prevalence and Risk Factors of Tuberculosis Among the Prisoners in Khuzestan, South-West Iran - Alavi, Seyed Mohammad (Jundishapur J Microbiol, 2014)
BACKGROUND: High prevalence of Tuberculosis (TB) among prisoners is reported as an alarming public health problem in the world, especially in the developing countries. OBJECTIVES: Since there is almost no information from TB in this population in Khuzestan province, the current study aimed to assess the prevalence and identify risk factors of TB among the prisoners of this region. PATIENTS AND METHODS: In a retrospective study, medical files of patients with Tuberculosis in Khuzestan Health Center (KHC), from 2005 to 2010, were studied. Patients with Pulmonary TB were placed in two groups as the Inmate Prison (IP) and Non-Inmate Prison (NIP) groups. Data extracted from the patients' records in the two groups were compared by SPSS software system using Chi square and Fisher exact tests. P-value was considered less than 0.05. RESULTS: From the reported 4562 patients with Tuberculosis, 363 (7.9%) were prison inmates at the time of TB diagnosis. Prevalence of TB cases among the prison inmates was 403.3 per 100'000.The annual TB case rate in the general population during this period was 16.4 per 100,000. Among the TB risk factors close contact [odds ratio (OR), 95% confidence interval (CI), 19.4, 8.9-41.8, P < 001] especially in the recent 2 years, injection drug use (IDU) [OR, 95% CI, 4.61, 1.7-12.4, P = 006], and Human Immunodeficiency Virus (HIV) infection [OR, 95% CI, 2.4, 1.1-5.0, P = 025] were more frequent in the prisoners than in the general population with TB. CONCLUSIONS: In the region under study the prevalence of TB among the prisoners was higher than the general population. The main risk factors for Pulmonary TB in this population were close contact, IDU and HIV infection.